2019
DOI: 10.1111/aogs.13525
|View full text |Cite
|
Sign up to set email alerts
|

Maternal cardiac function, uterine artery hemodynamics and natriuretic peptides at 22‐24 weeks of gestation and subsequent development of hypertensive disorders of pregnancy

Abstract: Introduction:Maternal cardiac dysfunction as well as abnormal uterine artery (UtA) Doppler are associated with hypertensive disorders of pregnancy (HDP), but their relation is unclear. We investigated the correlation between maternal cardiac function, UtA hemodynamics and natriuretic peptides, and explored differences between women who subsequently developed HDP and those who did not. Material and methods:This was a prospective cross-sectional cohort study of 347 pregnant women at 22-24 weeks. Maternal card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Of those, 3122 individuals (32.0%) experienced an HDP, including 939 (9.6%) with gestational hypertension, 2167 (22.2%) with preeclampsia, and 16 (0.2%) without information on HDP subtype. The most frequently tested biomarker was NT-proBNP (n = 8940; 30 studies), followed by Gal-3 (n = 921; 11 studies), HSP27 (n = 363; 5 studies), and CD40 (n = 81; 2 studies). CSTB and ECP were both evaluated by a single study including 66 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Of those, 3122 individuals (32.0%) experienced an HDP, including 939 (9.6%) with gestational hypertension, 2167 (22.2%) with preeclampsia, and 16 (0.2%) without information on HDP subtype. The most frequently tested biomarker was NT-proBNP (n = 8940; 30 studies), followed by Gal-3 (n = 921; 11 studies), HSP27 (n = 363; 5 studies), and CD40 (n = 81; 2 studies). CSTB and ECP were both evaluated by a single study including 66 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings are consistent with the theory that reduced total UtA flow rate to the placenta is linked with poor pregnancy outcome. While studies of US-based measurements of UtA flow have reported lower flow in cases of PE [23][24][25][26] and SGA 27,28 , technical challenges have precluded the clinical use of US-based UtA flow. US is more operator-dependent than is MRI, and is sensitive to body habitus, angle of insonation and instrument gain artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…US is more operator-dependent than is MRI, and is sensitive to body habitus, angle of insonation and instrument gain artifacts. As lumen diameter is a significant contributor to accurate measurement of flow, measurements may be difficult to reproduce, since lumen walls may not always be resolved clearly 23 . Furthermore, since the UtAs are often tortuous, absolute measures, such as flow rate, that depend on measurement angle, are challenging to obtain 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, MRproANP has been found to be inversely associated with incident type 2 diabetes 16 . In uncomplicated pregnancies MRproANP plasma concentrations are similar or slightly higher than in the nonpregnant state, and MRproANP concentrations have been shown to be elevated in the clinical phase of preeclampsia, likely due to the strain on the heart that preeclampsia exerts 9,17–19 …”
Section: Introductionmentioning
confidence: 99%
“…16 In uncomplicated pregnancies MRproANP plasma concentrations are similar or slightly higher than in the nonpregnant state, and MRproANP concentrations have been shown to be elevated in the clinical phase of preeclampsia, likely due to the strain on the heart that preeclampsia exerts. 9,[17][18][19] MRproANP levels in the first trimester have not been investigated extensively, and most of the published studies focus on the MRproANP in the second and third trimester. Inconsistent results have been found, but some studies have shown elevated concentrations of MRproANP from 22 weeks of gestation in the preclinical phase of preeclampsia.…”
Section: Introductionmentioning
confidence: 99%